2020
DOI: 10.3390/biology9050107
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dynamic Structures of 2019-nCoV with Nonlocal Operator via Powerful Computational Technique

Abstract: In this study, we investigate the infection system of the novel coronavirus (2019-nCoV) with a nonlocal operator defined in the Caputo sense. With the help of the fractional natural decomposition method (FNDM), which is based on the Adomian decomposition and natural transform methods, numerical results were obtained to better understand the dynamical structures of the physical behavior of 2019-nCoV. Such behaviors observe the general properties of the mathematical model of 2019-nCoV. This mathematical model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
84
0
1

Year Published

2020
2020
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(85 citation statements)
references
References 65 publications
0
84
0
1
Order By: Relevance
“…For the Kawahara equation, recently Cui et al [63] derived the local well-posedness with−1 < s < 0 when = 0. Moreover, the time-fractional B-L equation is analyzed with various methods including, Variational iteration methods and Homotopy perturbation [60], Residual power series method [64], Reduced differential transform method [61], and others [14,17,24,[65][66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…For the Kawahara equation, recently Cui et al [63] derived the local well-posedness with−1 < s < 0 when = 0. Moreover, the time-fractional B-L equation is analyzed with various methods including, Variational iteration methods and Homotopy perturbation [60], Residual power series method [64], Reduced differential transform method [61], and others [14,17,24,[65][66][67][68][69][70][71][72].…”
Section: Introductionmentioning
confidence: 99%
“…Fractional calculus based on differential and difference equations is of considerable importance due to their connection with real-world problems that depend not only on the instant time but also on the previous time, in particular, modeling the phenomena by means of fractals, random walk processes, control theory, signal processing, acoustics, and so on (see [1][2][3][4][5][6][7][8][9][10][11][12]). It has been shown that fractional-order models are much more adequate than integer-order models.…”
Section: Introduction and Prelimnariesmentioning
confidence: 99%
“…Nonlinear differential (DEs) and integro-differential equations (IDEs) have a great importance in modeling of many phenomena in physics and engineering [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Fractional differential equations involving the Caputo and other fractional derivatives, which are a generalization of classical differential equations, have attracted widespread attention [18][19][20][21][22][23][24][25]. In the last decade or so, several studies have been carried out to develop numerical schemes to deal with fractional integro-differential equations (FIDEs) of both linear and nonlinear type.…”
Section: Introductionmentioning
confidence: 99%